the Effectiveness of the Rehabilitation Program on the ROM Articulatio Genu Post-Surgery Meniscus Menisectomy Patients at SPPOI Eminence Jakarta - Zahroh, Isna Lailatuz; Firdyansyah, Teddy; Khamdani, Yazid Rizki (Universitas Negeri Semarang, 2022)
Meniscus tear is the second-highest knee injury after ligament injury. Post-surgery meniscus menisectomy is one of the acts performed when the meniscus is injured or torn. After surgery requires a beneficial rehabilitation program to restore knee function as previously required, minimize the risk of Osteoarthritis (OA) and prevent further imposition on the knee. The study is a quantitative experiment using purposive sampling with one group of pre-test post-test. Population all patient SPPOI Eminence. The sample 10 people with details of 7 men and 3 women. Average results of Flexi ROM Articulatio Genu pre-test 98,40o±5,19 with extension ROM Articulatio Genu pre-test 6,60o±1,65. Further, rehabilitation programs (composed of modality therapy, manual therapy, and strengthening) were given a result of flexion ROM Articulatio Genu post- test 135,40o±4,88 and extension ROM Articulatio Genu post-test 1,70o±1,41. Data analysis showed an increase in degrees of flexion 34o and a decrease in extension 4,90o. Complete the T- test with Paired Sample T-test value flexion ROM Articulatio Genu with P ≤ 0,05 and value extension ROM Articulatio Genu with P ≤ 0,05. The rehabilitation programs consisted of modality therapy, manual therapy, and strengthening is effective to increase Range of Motion of Articulatio Genu in SPPOI Eminence patient.